AUGcontext DB: a comprehensive catalog of the mRNA AUG initiator codon context across eukaryotes - Vincent G. Osnaya; Laura Gómez-Romero; Gabriel Moreno-Hagelsieb; Greco Hernández (RNA Biology)
The mRNA translation defines the composition of the cell proteome in all forms of life and diseases. In this process, precise selection of the mRNA translation initiation site (TIS) is crucial, as it establishes the correct open reading frame for triplet decoding. We have gathered and curated all published TIS consensus context sequences. We also included the TIS consensus context from novel 538 fungal genomes available from NCBI’s RefSeq database. To do so, we wrote ad hoc programs in PERL to find and extract the TIS for each annotated gene, plus ten bases upstream and three downstream. For each genome, the sequences around the TIS of each gene were obtained, and the consensus was further calculated according to the Cavener rules and by the LOGOS algorithm. We created AUGcontext DB, a portal with a comprehensive collection of TIS context sequences across eukaryotes in a range from −10 to + 6. The compilation covers species of 30 vertebrates, 17 invertebrates, 25 plants, 14 fungi, and 11 protists studied in silico; 23 experimental studies; data on biotechnology; and the discovery of 8 diseases associated with specific mutations. Additionally, TIS context sequences of cellular IRESs were included. AUGcontext DB belongs to the National Institute of Cancer (Instituto Nacional de Cancerología, INCan), Mexico, and is freely available at http://108.161.138.77:8096/. Our catalogue allows us to do comparative studies between species, may help improve the diagnosis of certain diseases, and will be key to maximize the production of recombinant proteins.